Analysis of Unemployment, Capita Income, and HDI on Economic Growth on Indonesia, 2017-2020.: Analisis Pengangguran, Pendapatan Perkapita, dan IPM Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2017-2020. - Sari, Sandra Dwita; Setyowati, Eni (Universitas Muhammadiyah Sidoarjo, 2022)
Economic growth is one of the important indicators to measure the level of progress and development in a country. This study aims to determine the effect of Unemployment, Per capita Income, and Human Development Index (IPM) on Economic Growth in Indonesia in 2017-2020. The analytical method used in this regression research is descriptive analysis and panel data analysis using Eviews 10 software, with secondary data obtained from the Central Statistics Agency (BPS) with a cross section covering 34 provinces in Indonesia which produces 136 observations, while the time series data starting in 2017-2020. The results showed that the 3 variables tested, Unemployment had a positive and significant effect on economic growth with a probability of 0.0000 < = 0.01, income per capita had a positive and significant effect on economic growth with a probability of 0.0000 < = 0.01, while the index Human Development (IPM) has a negative and significant effect on economic growth with a probability of 0.0542 < = 0.10. The results of the study of the coefficient of determination (R2) also show good results, where 86% of the variation in the growth dependent variable can be explained by the independent variables of Unemployment, Per capita Income and Human Development Index (IPM). While the remaining 13.83% is explained by other variables that are not included in the model.